Analisasi Konsep Kekuasaan Dalam Teori Politik Dan Demokrasi - Bella Ayu Anzalia; Deo Agung Haganta Barus; Limra GM Nababan; Nur Hidayah Hasibuan; Julia Ivanna (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
This research is to understand the concept of power in political and democratic theory. This research uses the method, In political theory, the concept of power refers to the ability of a person or group to influence the actions, decisions and behavior of other people. This concept is important in understanding how power is used and distributed in a political system. In political theory, power is understood as the ability to influence the actions and decisions of others, with various approaches, including as a resource or as a social relationship.